Press access to public information in the light of administrative courts’ case law - Nosarzewski, Łukasz (Ius Novum, 2025)
This article deals with the issue of press access to public information. It presents the thesis that press access to public information, in comparison to the general rules applicable to ordinary citizens, has been limited by additional non-statutory formal requirements. This thesis is supported by numerous judgments of administrative courts regarding the disclosure of public information. This limitation primarily resulted from changes in the interpretation of regulations that have been in force for years and their application by administrative courts and, in part, from changes in the regulatory environment. Therefore, it is postulated that the journalistic right to information should be strengthened, and the function and mission of the press should be recognised to actualise citizens’ rights to reliable information, openness of public life, and social control and criticism. The article employs the dogmatic and legal analysis method and an analysis of Polish administrative courts’ case law.